Will GDP growth increase happiness in developing countries? - Andrew E. Clark; Claudia Senik (Institute for the Study of Labor (IZA), 2011)
This paper asks what low-income countries can expect from growth in terms of happiness. It interprets the set of available international evidence pertaining to the relationship between income growth and subjective well-being. Consistent with the Easterlin paradox, higher income is always associated with higher happiness scores, except in one case: whether growth in national income yields higher well-being is still hotly debated. The key question is whether the correlation coefficient is too small to matter. The explanations for the small correlation between national income growth and subjective well-being over time appeal to the nature of growth itself (from negative side-effects, such as pollution), and to the psychological importance of relative concerns and adaptation. The available evidence contains two important lessons: income comparisons do seem to affect subjective well-being, even in very poor countries; however, adaptation may be more of a rich-country phenomenon. Our stand is that the idea that growth will increase happiness in low-income countries cannot be rejected on the basis of the available evidence. First, cross-country time-series analyses are based on aggregate measures, which are less reliable than those at the individual level. Second, development is a qualitative process involving take-off points and thresholds. Such regime changes are visible to the eye through the lens of subjective satisfaction measures. The case of Transition countries is particularly impressive in this respect: average life satisfaction scores closely mirrored changes in GDP for about the first ten years of the transition process, until the regime became more stable. The greater availability of subjective measures of well-being in low-income countries would greatly help in the measurement and monitoring of the different stages and dimensions of the development process.
urn:nbn:de:101:1-201104134176
Keywords: D63; I3; O1; 330; income; subjective well-being; comparisons; adaptation; development; Zufriedenheit; Wirtschaftswachstum; Entwicklung; Soziale Beziehungen; Entwicklungsländer